2023
DOI: 10.2217/nnm-2022-0228
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing The Antischistosomal Activity of Carvacryl Acetate Using Nanoemulsion

Abstract: Aim: To formulate a carvacryl acetate nanoemulsion (CANE) and test its antischistosomal activity. Materials & methods: CANE was prepared and tested in vitro on Schistosoma mansoni adult worms and both human and animal cell lines. Next, CANE was administered orally to mice infected with either a prepatent infection or a patent infection of S. mansoni. Results: CANE was stable during 90 days of analysis. CANE showed in vitro anthelmintic activity, and no cytotoxic effects were observed. In vivo, CANE was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…4K-UHD monitor system (LG Electronics, Taubaté, SP, Brazil). 38 Larval motility, scored for an effect ≥60%, was categorized as follows: 1 (immotile), 2 (intermittent head or tail shaking), 3 (sluggish and motile), and 4 (highly active and motile). 14 Images were captured using a Motic AE2000 inverted microscope (Vancouver, Canada) equipped with a Motic ultrahigh definition (UHD) camera.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4K-UHD monitor system (LG Electronics, Taubaté, SP, Brazil). 38 Larval motility, scored for an effect ≥60%, was categorized as follows: 1 (immotile), 2 (intermittent head or tail shaking), 3 (sluggish and motile), and 4 (highly active and motile). 14 Images were captured using a Motic AE2000 inverted microscope (Vancouver, Canada) equipped with a Motic ultrahigh definition (UHD) camera.…”
Section: Methodsmentioning
confidence: 99%
“…Larval viability was assessed immediately post drug addition (time 0) and after 2, 6, 12, and 24 h using an inverted microscope (BEL Engineering INV100, Monza, MB, Italy) equipped with a BEL Engineering ultrahigh definition (UHD) camera and a 48 in. 4K-UHD monitor system (LG Electronics, Taubaté, SP, Brazil) . Larval motility, scored for an effect ≥60%, was categorized as follows: 1 (immotile), 2 (intermittent head or tail shaking), 3 (sluggish and motile), and 4 (highly active and motile) .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our group demonstrated that the nanoemulsification process improves the anthelmintic activity of CA via oral administration using a model of mice infected with Schistosoma mansoni [ 27 ]. In the present work, the influence of the mixture of surfactants on the stability of the CA nanoemulsion (CANE) was studied.…”
Section: Introductionmentioning
confidence: 99%